Estudantes na condição de altas habilidades/superdotação: tecendo compreensões e (seus) sentidos - Santos, Rosalva Maria Martins dos (2023)
The aim of this study is to analyze experiences of students with high abilities/giftedness in school and family dynamics through the Eliasian and Freudian constructs. It developed based on figurational assumption of sociology elaborated by Norbert Elias in association with Sigmund Freud’s psychoanalysis and it was taken as a study path the concepts of figuration, knowledge, language, desire for learning (ELIAS, 1993, 1994, 1995, 2009), drive, sublimation, desire and demand to know (FREUD, 1905, 1908, 1910, 1915). It conducted predominantly quantitative research, adopting conversation as methodology from the perspective of figurational sociological theory. Due to the ongoing pandemic situation, the conversations took place virtually on Google Meet platform, were recorded and later transcribed. Due to the pandemic moment we were experiencing the conversations took place virtually through the Google Meet platform and they were recorded and subsequently transcribed. The conversations involved adolescents between ages of 16 and 17 years, "students with high abilities/giftedness", who were enrolled in public schools of common education in the metropolitan region of Grande Vitória in the state of Espírito Santo. The participants also included the students’ families and their teachers who worked in the common classroom and in the multifunctional resource room. Considering the figurational dynamics within the school and families, the aim through these conversations was to understand how students who experience high abilities/giftedness navigate their impulse investments. The systematized data in this study makes it possible to understand high abilities/giftedness as a distinct condition that arises within the emotional dynamics of human interrelations. More prominently, the condition of high abilities is constituted through a process of sublimation specific emotions that, experienced more intensely by certain individuals amidst the tensions that characterize the dynamics of their own interrelations interrelations, drive a libidinal investment towards activities valued within a historical, cultural and social process. In accordance with Elias (2009), it was understood that the condition of high abilities manifests through the interplay between the biological and the social, between the first nature and the second nature. In the complex process of forming second nature, which is predominantly shaped by historical and cultural factors, people may undergo experiences that remarkably enhance their predisposition for the optimal development of their intellectual abilities derived from their first nature, which is primarily biological. Through the conversations with students experiencing high abilities/giftedness, it was observed that specialized educational care has played a significant role in their formative processes, since the students have channeled their libidinal drives into activities that bring them pleasure and stimulate learning. It was also noticed that within the family dynamics, the potential and abilities of these students were initially stimulated to a limited extent, and their libidinal drives were directed towards activities that sparked their interest and expanded their social background of knowledge. Regarding their experiences in the regular classroom, it was observed that, despite encountering adverse situations, such as conflicts and tensions, the students were still in able to invest their drives in activities where the desire for knowledge and learning could be stimulated and, therefore, in certain situations, they were able to engage in activities that met their intellectual needs and desires.